2009
DOI: 10.1165/rcmb.2008-0290oc
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Mammalian Target of Rapamycin Complex 1 in Toll-Like Receptor 2– and 4–Induced Neutrophil Activation and Acute Lung Injury

Abstract: mTOR complex 1 (mTORC1) plays a central role in cell growth and cellular responses to metabolic stress. Although mTORC1 has been shown to be activated after Toll-like receptor (TLR)-4 engagement, there is little information concerning the role that mTORC1 may play in modulating neutrophil function and neutrophil-dependent inflammatory events, such as acute lung injury. To examine these issues, we determined the effects of rapamycin-induced inhibition of mTORC1 on TLR2-and TLR4-induced neutrophil activation. mT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
84
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 43 publications
7
84
0
2
Order By: Relevance
“…Rapamycin also reverses congenital hypertrophic cardiomyopathy in juvenile mice manifesting LEOPARD syndrome (29). Furthermore, TLR4-or TLR2-induced neutrophil activation and lung injury resulting from increased mTORC1 signaling is attenuated by rapamycin treatment (30). It is interesting to note that inflammatory signals resulting from TLR4 or TRL2 activation is a potential cause of preterm birth (31).…”
Section: Discussionmentioning
confidence: 99%
“…Rapamycin also reverses congenital hypertrophic cardiomyopathy in juvenile mice manifesting LEOPARD syndrome (29). Furthermore, TLR4-or TLR2-induced neutrophil activation and lung injury resulting from increased mTORC1 signaling is attenuated by rapamycin treatment (30). It is interesting to note that inflammatory signals resulting from TLR4 or TRL2 activation is a potential cause of preterm birth (31).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that inhibition of mTOR decreases the production of proinflammatory cytokines, inhibits the phosphorylation of the NFkB p65 subunit, and attenuates acute lung injury after intratracheal LPS administration (Lorne et al 2009). A previous report has shown that inhibition of NFkB attenuated the reductions in body weight and food intake induced by tumors (Kawamura et al 1999).…”
Section: Crosstalk Of the Mtor And Nfkb Pathways In Lps-induced Anorexiamentioning
confidence: 99%
“…It has been reported that rapamycin decreased the severity of lung injury after intratracheal LPS or PAM administration, as determined by diminished neutrophil accumulation in the lungs and reduced interstitial pulmonary edema (18). The downregulation of autophagy may lead to systemic inflammation and ALI following sepsis.…”
Section: Discussionmentioning
confidence: 99%